Pengaruh Media Pembelajaran Power Point Terhadap Minat Belajar Sejarah Siswa - Dona Fitriyani; Tontowi Tontowi; Muhammad Basri (FKIP UNIVERSITAS LAMPUNG, 2017)
The purpose of the research is to find out whether or not there is an increase on students' learning interest in History subject using Power Point learning media for students of Tenth graders of Senior High School (SHS) Gajah Mada Bandar Lampung academic year 2016/2017. This research used experimental method. The data analysis technique was carried out using qualitative data analysis by means of formula percentage. The results of the data analysis and discussion concluded that the use of Power Point learning media influenced the increase of students' learning interest in History subject for grade X of Senior High School (SHS) Gajah Mada Bandar Lampung academic year 2016/2017. Tujuan Penelitian untuk mengetahui ada tidaknya peningkatan minat belajar siswa pada Mata Pelajaran Sejarah menggunakan media pembelajaran Power Point Kelas X SMA Gajah Mada Bandar Lampung Tahun Ajaran 2016/2017. Metode yang digunakan metode eksperimen. Teknik analisis data adalah teknik analisis data kualitatif dengan menggunakan rumus persentase. Hasil analisis data dan pembahasan dapat disimpulkan bahwa penggunaan media pembelajaran Power Point berpengaruh terhadap peningkatan minat belajar siswa pada Mata Pelajaran Sejarah kelas X SMA Gajah Mada Bandar Lampung Tahun Ajaran 2016/2017.Kata kunci: minat, pengaruh, power point